Strongly-correlated lattice systems on a finite cylinder - Rosson, P (2019)
In this thesis, I present my research on the numerical simulation of finite-size strongly-correlated lattice systems using the density matrix renormalisation group (DMRG). Ultracold gases in optical lattices have become the experimental setup of choice to simulate models from condensed-matter physics, because of their high degree of tunability and control. Their inherently finite size and alternative implementation call for a more in-detail study of how to define and characterise the phases of the models that they simulate.